IMPROVING THE ACTIVATION OF SYNONYMS IN PRIMARY SCHOOL STUDENTS’ SPEECH - Rustamova Davlatkhan Toyirjon qizi (Web of Journals Publishing, 2024)
This article analyzes the process of improving the model of the activation of meaningful words in the speech of students of junior school age. Students' lack of vocabulary, lack of knowledge of the dictionary meaning of a word in their mother tongue, and lack of concepts about a series of words with the same meaning cause problems like the above. Taking into account that this period is the main stage for students to form a linguistic personality and learn to communicate with others from the primary education age, it is believed that it is necessary to pay attention to increasing the vocabulary of primary school students and teaching them to distinguish the meanings of words from this period.
Keywords: primary education, synonyms, vocabulary, word meanings, modern technologies, analysis, stepwise feature, modeling, synthesis, integrated vision, classification, design, comparison, grouping.